Peran Muhammadiyah Dalam Pencegahan Dan Pemberantasan Tindak Pidana Korupsi Di Kota Batu - Tinuk Dwi Cahyani; Sholahuddin Al-Fatih (Universitas Muhammadiyah Surabaya, 2020)
In effort to prevent and eradicate corrupt behavior, the community also has rights and obligations, in the sense that the community seeks to prevent and eradicate criminal acts of corruption. One form of community participation in preventing and eradicating corruption is through community organizations (Ormas). Ormas are considered as a forum for people who are engaged in social affairs and those who are neutral and do not have a practical political orientation. This research is a type of legal research using primary data, secondary data and tertiary data. Corrupt mentality of course comes from the motivation to rule on the basis of excessive ambition and precisely indirectly facilitated by the existing political system conditions, I think it is quite simple when someone who wants to get a higher position, the